Assessing the Impact of Sequential Data Presentation on Specific Learning Disabilities Identification Decisions Using Patterns of Strengths and Weaknesses Methods. (June 2021) - Maki, Kathrin E.; McGill, Ryan J.; Conoyer, Sarah J.; Fefer, Sarah A.; Ward, Thomas
Patterns of strengths and weaknesses represent relatively novel methods for identifying specific learning disabilities (SLD) with proponents asserting that the incorporation of multiple sources of assessment data and professional judgment play a key role in their utility. In this study, we examined if the sequential presentation of assessment data impacted school psychologists' ratings as to whether or not hypothetical students depicted in special education evaluation vignettes should be identified with SLD. Results showed that when participants viewed vignettes that were indicative of SLD (i.e., SLD positive), SLD likelihood ratings increased with the additional presentation of assessment data sources over time. However, when participants viewed vignettes that were indicative of a student not having SLD (i.e., SLD negative), SLD likelihood ratings were relatively consistent over time. Moreover, participants demonstrated relatively high levels of confidence in their SLD identification decisions, and in SLD negative vignettes, confidence increased after the fourth assessment data source was presented. Implications for SLD identification are discussed.